Balancing trade-offs between nutritional quality, consumer acceptability and climate impact across a spectrum of chili con carne formulations: from plant-based to hybrid - Wollmar, Mari; Post, Anna; Elf, Maja; Ingridsdotter, Josephine; Prim, Mia; Sjöberg, Agneta (Frontiers in Nutrition, 2025)
IntroductionTransitioning to sustainable food consumption, through nutritious and low carbon diets, is essential to address climate and health challenges. Current trends indicate an increase of plant-based meals in schools. However, these climate-friendly options are not consistently well-received by students and often fail to meet dietary iron requirements, particularly for adolescent girls. This study aims to develop a methodology for creating sustainable school meal recipes that balance absorbable iron, carbon footprint, and taste preferences.MethodsThe methodology involves iterative recipe development, including cooking elaborations and consumer evaluations. A chili con carne recipe was selected as the test dish where various plant-based and meat hybrid alternatives were assessed. Absorbable iron was calculated using the Hallberg and Hulthén algorithm, factoring in inhibitors and enhancers. Consumer evaluations were conducted in two rounds with university staff and students as a methodological validation step, involving sensory assessments and preference tests.ResultsThe study found substantial differences between total iron content and absorbable iron, with plant-based recipes (Soy1) achieving only 35% of the required absorbable iron for high-need teenage girls despite meeting total iron requirements. Hybrid recipes incorporating both meat and plant-based ingredients showed better iron bioavailability and were more acceptable to consumers. Optimized recipes reduced carbon footprint by 16–84% compared to the original recipe, with hybrid recipes (Beef/Soy and Beef/Lentils) achieving 37–39% reductions while maintaining adequate absorbable iron levels (0.42–0.56 mg per meal vs. 0.44–0.66 mg target range).Discussion/ConclusionThe findings suggest that hybrid recipes can effectively balance absorbable iron, carbon footprint and taste preferences to promote sustainable and healthy eating habits among adolescents. Validation with the target adolescent population in school settings is recommended as the essential next step.